CD99 regulates neural differentiation of Ewing sarcoma cells through miR-34a-Notch-mediated control of NF-kB signaling - Ventura, Selena (Oncogene, 2015)
Sarcomas are mesenchymal tumors characterized by blocked differentiation process. In Ewing sarcoma (EWS) both CD99 and EWS-FLI1 concur to oncogenesis and inhibition of differentiation. Here we demonstrate that uncoupling CD99 from EWS-FLI1 by silencing the former, NF-kB signaling is inhibited and the neural differentiation program is re-established. NF-kB inhibition passes through miR-34a-mediated repression of Notch pathway. CD99 counteracts EWS-FLI1 in controlling NF-kB signaling through the miR-34a, which is increased and secreted into exosomes released by CD99-silenced EWS cells. Delivery of exosomes from CD99-silenced cells was sufficient to induce neural differentiation in recipient EWS cells through miR-34a inhibition of Notch-NF-kB signaling. Notably, even the partial delivery of CD99 siRNA may have a broad effect on the entire tumor cell population thanks to the spread operated by their miR-34a-enriched exosomes, a feature opening to a new therapeutic option.